2019
DOI: 10.3390/plants8100386
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Genome Sequencing of Sedum plumbizincicola Sheds Light on the Structural Evolution of Plastid rRNA Operon and Phylogenetic Implications within Saxifragales

Abstract: The genus Sedum, with about 470 recognized species, is classified in the family Crassulaceae of the order Saxifragales. Phylogenetic relationships within the Saxifragales are still unresolved and controversial. In this study, the plastome of S. plumbizincicola was firstly presented, with a focus on the structural analysis of rrn operon and phylogenetic implications within the order Saxifragaceae. The assembled complete plastome of S. plumbizincicola is 149,397 bp in size, with a typical circular, double-strand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 108 publications
(102 reference statements)
2
7
0
Order By: Relevance
“…According to the Angiosperm Phylogeny Group (APG) system IV [ 118 ], the order Saxifragales includes 15 families. Our mitophylogenetic tree divided 16 species into two clades and five families, which were generally congruent with the framework phylogeny of Saxifragales reported by Folk et al (nuclear data) [ 119 ], Ding et al (plastid data) [ 51 ], and Han et al (plastid data) [ 120 ]. Nevertheless, there are still some unsolved phylogenetic problems within Saxifragales.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…According to the Angiosperm Phylogeny Group (APG) system IV [ 118 ], the order Saxifragales includes 15 families. Our mitophylogenetic tree divided 16 species into two clades and five families, which were generally congruent with the framework phylogeny of Saxifragales reported by Folk et al (nuclear data) [ 119 ], Ding et al (plastid data) [ 51 ], and Han et al (plastid data) [ 120 ]. Nevertheless, there are still some unsolved phylogenetic problems within Saxifragales.…”
Section: Discussionsupporting
confidence: 90%
“…For example, the exact taxonomic position of S. plumbizincicola is not entirely clear. Ding et al [ 51 ] indicated that the S. plumbizincicola mitogenome was close to S. sarmentosum Bunge. Han et al [ 120 ] subsequently implied that S. plumbizincicola had a closer relationship with S. tricarpum Makino than S. sarmentosum by increasing sampling size.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In angiosperms, the plastid genome (plastome) generally exhibits a conserved quadripartite circular structure with a size of 120–170 kb, comprising two single copy regions (larger and small regions, namely LSC and SSC, respectively) and two inverted repeat regions (IRs) [ 14 , 15 , 16 ]. Owing to the low level of recombination, uniparental inheritance, and without interference from paralogs, plastome has been extensively utilized as a super-barcode for plant species identification and evolutionary studies [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Due to the rapid development and widespread application of high-throughput sequencing technologies (such as Illumina, PacBio, and Nanopore sequencing technologies), an increasing number of complete Crassulaceae plastomes (more than 70 sequences) have been deposited in public databases.…”
Section: Introductionmentioning
confidence: 99%